Comparison of a pediatric-inspired treatment protocol versus standard-intensity chemotherapy for young adults with standard-risk BCR-ABL negative acute lymphoblastic leukemia. Issue 4 (3rd April 2017) - Kliman, David; Barnett, Michael; Broady, Raewyn; Forrest, Donna; Gerrie, Alina; Hogge, Donna; Nantel, Stephen; Narayanan, Sujaatha; Nevill, Thomas; Power, Maryse; Sanford, David; Song, Kevin; et al.
Abstract: We investigated the utility of a pediatric-inspired protocol in adults aged 18–40 years with standard-risk BCR-ABL negative acute lymphoblastic leukemia (ALL). Retrospective outcomes of 25 patients treated with a pediatric protocol between 2008 and 2014 were compared with 22 similarly aged patients treated with an adult protocol between 2003 and 2008. Twenty-five (100%) and 19 (86%) patients achieved complete remission, respectively. At median follow-up of 36.8 months, 3-year event-free survival was increased in patients on the pediatric protocol at 80% versus 45% ( p = .019). There was a trend toward improved overall survival at 80% versus 59% ( p = .12). Treatment-related toxicity was not increased despite the increased treatment intensity. Patients with BCR and/or ABL copy number variation demonstrated comparatively poorer outcomes in both cohorts. In our experience with this cohort of patients, pediatric-based protocols are safe and effective, justifying their use in younger adults with ALL.